Neuromuscular adaptations to resistance training in elite versus recreational athletes - Sumaira Aslam; Jean De Dieu Habyarimana; Shi Yong Bin (Frontiers in Physiology)
Neuromuscular adaptations to resistance training drive strength and performance improvements, but differences between elite and recreational athletes remain underexplored. Understanding the underlying mechanisms can refine training approaches and enhance athletic development. This review synthesized findings from the past decade regarding how training status, age, sex, and genetics influence neuromuscular adaptations to resistance training, identified key gaps in the literature, and provided practical recommendations for tailoring training to different athletic levels. This critical review synthesized evidence on neuromuscular adaptations to resistance training, focusing on muscle hypertrophy, architectural changes, motor unit recruitment, neural drive, fiber-type transitions, and genetic influences. Methodological limitations and gaps were highlighted, with a focus on elite versus recreational populations. Muscle hypertrophy and strength gains occur rapidly in novices but plateau in advanced athletes, requiring more complex stimuli. Neural adaptations, including improved motor unit synchronization and reduced antagonist co-contraction, distinguish elite from recreational athletes. Genetic predispositions and training history further modulate adaptations. Fatigue, recovery, and injury risk differ between groups, underscoring the need for tailored monitoring and recovery strategies. Research gaps include inconsistent methodologies, limited elite athlete data, and underrepresentation of female cohorts. Future studies should integrate neurophysiological tools and long-term designs to clarify these mechanisms. Effective training requires adjusting intensity and volume based on an athlete’s training status. Foundational strength programs benefit youth, while elite athletes require periodization and advanced methods. Policy-level support for supervised resistance training in youth can enhance performance and injury resilience. Addressing these insights can optimize training outcomes across athletic levels.